Comparison between Elderly Adults and Adults: Emotions, Social-cultural Level, Memory Capacity Perception and Performance in Memory Task - Schade Y., Nieves; Gutiérrez G., Berta; Uribe V., Marcela; Sepúlveda S., Claudia; Reyes N., Carolina (Revista de Psicología, 2003)
The aim of this research was to compare the relationship of emotions, social- cultural level, perception of memory capacity and performance in memory tasks, between elderly and younger adults. The participants were 257 subjects (100 older adults and 157 adults), 30 to 87 years of age. The instruments employed were Memory Test, a Perception Test and Questionaire. Results were analyzed using correlational methods. The results show significant positive correlations between age and perception of procedural memory and semantic memory capacity, and a negative one with working memory processes. Also, a significant negative correlation was found between age and performance in memory tasks, including the subsystems of operative, episodic and semantic memory. Moreover, a significant positive correlation was found between the perception of memory capacity and socio-cultural level, but not so in performance. Finally, a positive correlation was found between the perception of capacity and performance in memory tasks. The importance of research concerning the influence of the sociocultural variables in memory performance was discussed.